Penerapan Sistem Informasi Manajemen BAZNAS (SIMBA) dalam Meningkatkan Transparansi Pengelolaan Dana Zakat di BAZNAS Kota Surabaya - Ayuni Putri, Jovita Adies (ZAWA: Management of Zakat and Waqf Journal, 2025)
This  study  aims  to  analyze  the  application  of  BAZNAS  Management  Information  System (SIMBA) in improving the transparency of zakat management in BAZNAS Surabaya City. Transparency is an important element in the governance of zakat institutions because it involves accountability for public funds and public trust, especially from muzakki. Lack of transparency is often the cause of low public participation in channeling zakat through official institutions. To answer this challenge, BAZNAS RI developed SIMBA as an integrated digital system that supports the recording, distribution, and reporting of zakat openly and efficiently. This research uses qualitative method with field research approach. Data were obtained through in-depth interviews with BAZNAS Surabaya, direct observation of the use of SIMBA, and review of financial documents and zakat distribution reports. The results show that SIMBA has a positive impact on transparency, through real-time reporting features, integration of muzakki and mustahik data, and ease of the audit process. In addition, SIMBA also accelerates reporting to the public and stakeholders. Nevertheless, challenges such as limited human resources, uneven technological infrastructure, and resistance to digitalization are still found. SIMBA is a strategic solution in improving transparency, but its implementation requires continuous support.